L’abandon et l’appel, ou l’optimisme paradoxal de Graham Greene dans The Power and the Glory - René Gallet (Revue LISA)
The Power and the Glory is often seen as a pessimistic, if not tragic, work. However, this fails to consider Greene’s little-known statement to the contrary, as well as important aspects of the novel, one of them being the idea of “glory” in the title. In the narrative itself, a fragmented presence of beauty can be discovered as early as the opening scene, and more particularly within Mr Tench’s seedy universe. Two contrasting worlds are thus intermingled from the very beginning, and the rest of the novel is interspersed with similar examples. A related observation can be made about the feeling of abandonment voiced by most of the characters. When examined more closely, the feeling turns out to be highly ambiguous, and not always devoid of bad faith. It should be contrasted with the repeated phenomenon of calls to responsible action. The most striking one is also found in the opening scene, where the fugitive priest is reminded of his duty by the mysterious, though seedy-looking, native child. And through the priest a call is addressed to Mr Tench, who fails to perceive anything. This call to his repressed conscience is repeated in the final scene when he witnesses the priest’s execution. Newman’s understanding of man’s condition probably underlies such contrasts “between the beautiful and the treacherous”. The degraded world in which most characters evolve is not to be isolated from the experience of conscience which both confirms the reality of this negative state of affairs and, in varying degrees, distances the characters from it.